TLR2 Activation by Porphyromonas gingivalis Requires Both PPAD Activity and Fimbriae - Wielento, Aleksandra; Bereta, Grzegorz P.; Łagosz-Ćwik, Katarzyna B.; Eick, Sigrun; Lamont, Richard J.; Grabiec, Aleksander M.; Potempa, Jan (Frontiers in Immunology, 2022)
Porphyromonas gingivalis, a keystone oral pathogen implicated in development and progression of periodontitis, may also contribute to the pathogenicity of diseases such as arthritis, atherosclerosis, and Alzheimer’s. P. gingivalis is a master manipulator of host immune responses due to production of a large variety of virulence factors. Among these, P. gingivalis peptidyl arginine deiminase (PPAD), an enzyme unique to P. gingivalis, converts C-terminal Arg residues in bacterium- and host-derived proteins and peptides into citrulline. PPAD contributes to stimulation of proinflammatory responses in host cells and is essential for activation of the prostaglandin E2 (PGE2) synthesis pathway in gingival fibroblasts. Since P. gingivalis is recognized mainly by Toll-like 2 receptor (TLR2), we investigated the effects of PPAD activity on TLR2-dependent host cell responses to P. gingivalis, and to outer membrane vesicles (OMV) and fimbriae produced by P. gingivalis. Using reporter cell lines, we found that PPAD activity was required for TLR2 activation by P. gingivalis cells and OMV. We also found that fimbriae, an established TLR2 ligand, from WT ATCC 33277 (but not from its isogenic PPAD mutant) enhanced the proinflammatory responses of host cells. Furthermore, only fimbriae from WT ATCC 33277, but not from the PPAD-deficient strains, induced cytokine production and stimulated expression of genes within the PGE2 synthesis pathway in human gingival fibroblasts via activation of the NF-ĸB and MAP kinase-dependent signaling pathways. Analysis of ten clinical isolates revealed that type I FimA is preferable for TLR2 signaling enhancement. In conclusion, the data strongly suggest that both PPAD activity and fimbriae are important for TLR2-dependent cell responses to P. gingivalis infection.